Analisis Dampak Pemberdayaan Perempuan terhadap Kesejahteraan Keluarga - Muhammad Muhyiddin Robani; Marlina Ekawaty (AL-MUZARA'AH, 2019)
This research was conducted to analyze: (1) the form of empowerment carried out by KJKS Ukhuwah Pro-IBU; and (2) the impact of empowerment carried out by KJKS Ukhuwah Pro-IBU. Mix methods with sequential exploratory model was used on this research. The results of the study through interview, observation, and documentaion shows that KJKS Ukhuwah Pro-IBU conducted empowerment through loans and financing with sharia contract, weekly meetings, and training for women groups that were formed. This results shows that the form of empowerment of KJKS Ukhuwah Pro-IBU can be classified as Economic Empowerment and Sharia Grameen. Based on multiple linier regression test, it is known that material welfare of KJKS Ukhuwah Pro-IBU members is positively influenced by financing, length of business, education and negatively by number of family members and age. On the other hand, other factors namely attendance at weekly meetings, Islamic business ethics, has no significant influence. As for the results of Pearson corellation test, it is known that non-material welfare has a relationship with other variables, namely a positive relationship with a moderate degree of closeness with variables of material welfare, financing, Islamic business ethics. This results shows that material or non material welfare improvement one of them can be achieved with women empowerment that using forms of economic empowerment and Sharia Grameen.